Molecular investigation of CTX-M gene in Extended Spectrum β Lactamases (ESBLs) producing Pseudomonas aeruginosa isolated from Iranian patients with burn wound infection - Piri, Fatemeh; Tajabadi Ebrahimi, Maryam; Amini, Kumarss (Archives of Medical Laboratory Sciences, 2019)
Background: Pseudomonas aeruginosa (P. aeruginosa) is one of the most important causes of infection in burns and intensive care units. Extended-spectrum β-lactamases (ESBLs) production in P. aeruginosa is a major factor in the antibiotic resistance and is thought of as a serious threat to the currently available antibiotic armory. The purpose of this study was to determine the prevalence of CTX-M gene in ESBL-producing P. aeruginosa isolates in burn wound samples. Materials and methods: In this cross-sectional survey, a total of 60 clinical isolates of P. aeruginosa were obtained from patients suffering from burn wound infection referred to major hospitals of Tehran, Iran. After verification by biochemical tests and antimicrobial susceptibility testing, CTX-M gene was identified using PCR method. Results: The results of the molecular analysis of CTX-M gene showed that the prevalence of isolates of P. aeruginosa harboring CTX-M gene was 20% (12/60). Conclusion: The results from this study showed high levels of antibiotic resistance and CTX-M gene among P. aeruginosa isolated samples of burn-wound infections which condition may result in the increased the emergence of multidrug-resistant strains and the failure of therapy This study suggests that detailed data on the CTX-M gene frequency can be useful to achieve the best therapy for infections caused by ESBLs producing P. aeruginosa.